К вопросу о знаковой роли посуды из раннебронзовых памятников Кавказа (конец IV-III тыс.) - Андреева, М.В.
engl. Résumé: On the Symbolic Role of Vessels from Early Bronze Monuments of the Caucasus (end of 4th-3rd mill. B.C.)